Development of Android Application based on 2D Animation for the Care of Down Syndrome Individuals - Hii, Li Hua; Mohd Razali, Nur Syamimi (Research and Innovation in Technical and Vocational Education and Training, 2024)
People with Down syndrome require discipline and care because their condition has shaped their way of life. The development of an Android application based on a 2D animated video aims to help individuals with Down syndrome in their daily lives and assist teachers or parents in caring for and educating them. The ADDIE model was used in the development of this product, consisting of five phases: analysis, design, development, implementation, and evaluation. In the analysis phase, developers analyzed the problems that occurred and identified the software and hardware requirements. In the design phase, the developer created a storyboard to be used as a reference during product development. During the development and implementation phases, developers built the product based on the storyboard. The evaluation and testing process was carried out by five experts in the field of creative multimedia from the Faculty of Technical and Vocational Education and the Methodist Care Center. The instrument used was an expert checklist form. Through the results of the study, all the experts provided positive feedback on the Android application based on the 2D animated video for the care of individuals with Down syndrome. The developed application has been accepted and works well.